Significance of Nonrespiratory Airflow During Swallowing - Brodsky, Martin B. (2011)
This study was designed to further our understanding of a potentially significant clinical event of negative nasal airflow near the end of the respiratory pause (inhibition) to accommodate swallowing. This negative flow, referred to as “SNIF,” or swallow noninspiratory flow, occurs at the onset of airway reestablishment at the conclusion of the oropharyngeal swallow. Using simultaneous digital video fluoroscopic and nasal respiratory air-flow recordings on 82 healthy adults (21–97 years old), the objectives of this study were to determine (1) the frequency of occurrence of SNIF during a 5-ml natural cup-drinking task, (2) differences in SNIF occurrence by age group, and (3) the temporal relationship between SNIF and other swallowing events. Results revealed that for most participants SNIF was observed in both swallowing trials. There was a statistically significant difference in SNIF occurrence by age category, with SNIF observed less frequently in the oldest participants. The peak onset of SNIF is closely related to the first release of contact between the soft palate and tongue base with the posterior pharyngeal wall and opening of the laryngeal vestibule. Based on this, and in agreement with previous investigators, we suggest that this negative flow may be related to a partial vacuum established by the relaxation of pharyngeal contraction near the conclusion of the pharyngeal swallow. The more frequent occurrence of SNIF in younger adults and less in older adults suggests a reduction in pharyngeal pressure associated with healthy aging.